Mini Tinjauan Literatur Pemanfaatan Software Tibi’s Mathematics Suite untuk Berpikir Komputasi Siswa - Nazira Ananda; Yahfizham Yahfizham (Konstanta : Jurnal Matematika dan Ilmu Pengetahuan Alam, 2025)
The development of information and communication technology (ICT) has opened up great opportunities in increasing the effectiveness of mathematics learning, especially in supporting students' computational thinking skills. This article presents a mini-literature review related to the use of Tibi's Mathematics Suite (TMS) as interactive software in mathematics learning. Using a descriptive qualitative approach and desk research method, this study analyzes various scientific sources to evaluate the contribution of TMS to the development of computational thinking, which includes decomposition, pattern recognition, abstraction, and algorithms. The results of the study show that TMS is able to increase students' interest in learning, independence, and metacognitive awareness, although its implementation still faces challenges such as limited infrastructure and teacher training. This review recommends the need for further empirical studies and education policy support so that the integration of TMS can be more optimal in the context of the Independent Curriculum and the strengthening of the Pancasila Student Profile.